US–China Geopolitical Tensions: Implications for Universities and Science - Li, Xiaojie; Lee, Jenny (International Higher Education, 2022)
Based on recent findings from a national survey involving about 2,000 faculty members, postdocs, and graduate students at top US universities, this article discusses the negative impact of US–China geopolitical tensions on the scientific community, including perceptions of equity, research collaboration, and scientist mobility.